Degradation of Methylparaben Using Optimal WO3 Nanostructures: Influence of the Annealing Conditions and Complexing Agent - M. Cifre-Herrando; G. Roselló-Márquez; D. M. García-García; J. García-Antón (Nanomaterials, 2022)
In this work, WO3 nanostructures were synthesized with different complexing agents (0.05 M H2O2 and 0.1 M citric acid) and annealing conditions (400 °C, 500 °C and 600 °C) to obtain optimal WO3 nanostructures to use them as a photoanode in the photoelectrochemical (PEC) degradation of an endocrine disruptor chemical. These nanostructures were studied morphologically by a field emission scanning electron microscope. X-ray photoelectron spectroscopy was performed to provide information of the electronic states of the nanostructures. The crystallinity of the samples was observed by a confocal Raman laser microscope and X-ray diffraction. Furthermore, photoelectrochemical measurements (photostability, photoelectrochemical impedance spectroscopy, Mott–Schottky and water-splitting test) were also performed using a solar simulator with AM 1.5 conditions at 100 mW·cm−2. Once the optimal nanostructure was obtained (citric acid 0.01 M at an annealing temperature of 600 °C), the PEC degradation of methylparaben (CO 10 ppm) was carried out. It was followed by ultra-high-performance liquid chromatography and mass spectrometry, which allowed to obtain the concentration of the contaminant during degradation and the identification of degradation intermediates. The optimized nanostructure was proved to be an efficient photocatalyst since the degradation of methylparaben was performed in less than 4 h and the kinetic coefficient of degradation was 0.02 min−1.